Synthesis and biology of 3 '-N-acyl-N-debenzoylpaclitaxel analogues - Roh, EJ; Song, CE; Kim, D; Pae, HO; Chung, HT; Lee, KS; Chai, KB; Lee, CO; Choi, SU (PERGAMON-ELSEVIER SCIENCE LTD, 1999)
The 3'-N-acyl-N-debenzoylpaclitaxel analogues 1a-d were synthesized and evaluated on biological systems. Some of the analogues 1a-d exhibited higher cytotoxicities (up to 20-fold) and stronger abilities to induce apoptosis than paclitaxel. In an in vivo experiment against ip implanted B16 melanoma, the most cytotoxic compound 1b in vitro caused tumor growth inhibition more than paclitaxel. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: PROGRAMMED CELL-DEATH; TAXOL ANALOGS; APOPTOSIS; CYTOTOXICITY; MICROTUBULES; CISPLATIN; THERAPY; CANCER; LINES